Method for improving electromigration reliability of lead-free interconnection welding spots based on ultrafast laser processing of hexagons

By using ultrafast laser processing on the copper surface of lead-free interconnect solder joints to prepare hexagonal array trench microstructures, the problem of long-term and poor reliability of solder joints is solved, and the electromigration reliability of solder joints is significantly improved.

CN119747782AActive Publication Date: 2025-04-04BEIJING UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510122083.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-04
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

The processing time and reliability of existing lead-free interconnect solder joints is long and the solder joints are poor, resulting in electromigration failure problems in high-power and highly integrated electronic devices.

Method used

The copper surface with a hexagonal array trench microstructure is prepared by ultrafast laser processing on the end surface of the welded body to be interconnected, thereby improving the surface area of ​​the connecting surface, and promoting uniform distribution of the series of solder materials and mechanical bonding after curing.

Benefits of technology

It significantly improves the electromigration reliability of lead-free interconnect solder joints, extends the failure time of solder joints, and improves the reliability of electronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005259127600000011
    Figure HDA0005259127600000011
  • Figure HDA0005259127600000012
    Figure HDA0005259127600000012
  • Figure HDA0005259127600000021
    Figure HDA0005259127600000021
Patent Text Reader

Abstract

The invention discloses a method for improving electromigration reliability of lead-free interconnection welding spots based on ultrafast laser processing of hexagons, and relates to the technical field of material processing and welding. A hexagonal array groove microstructure is prepared on the end face of a welding body to be interconnected by adopting an ultrafast laser processing technology, the hexagonal array groove microstructure is composed of a plurality of independent hexagonal linear groove units, and the hexagonal linear groove units are linear grooves corresponding to six sides of a hexagon. The outer side of each edge of each hexagonal linear groove unit is correspondingly provided with another hexagonal linear groove unit, and a gap is formed between the edges of every two adjacent hexagonal linear groove units; and then lead-free interconnection welding is adopted, so that the electromigration reliability is improved. The multi-scale hexagonal array-shaped micro-nano structure effectively improves the surface area of a connecting surface, is beneficial to uniform distribution of series brazing filler metal and mechanical combination after solidification, and is used for solving the problem that existing linear welding spots are poor in electromigration failure performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of material processing and welding, and in particular to a method for improving the electromigration reliability of lead-free interconnect solder joints based on ultrafast laser processing. Background Art

[0002] As electronic devices develop towards high power and high integration, the packaging density continues to increase, and the interconnection structure between electronic components has put forward higher requirements for its electromigration failure performance. The reduction in the size of solder joints will lead to electromigration problems. The research on the electromigration reliability of micro solder joints is an important research direction in the field of microelectronic packaging technology, which focuses on the stability and reliability of solder joints under various working conditions. Electromigration (EM) refers to the structural changes and diffusion phenomena of metal materials caused by electron migration when current passes through solder joints, which may lead to failure and performance degradation of solder joints, seriously affecting the reliability of electronic products. At present, the electromigration failure performance of welded joints can be effectively improved by preparing composite solders and optimizing welding processes. However, the existing technology still has many limitations in practical applications, and a more effective solution is urgently needed. Summary of the invention

[0003] The present invention provides a method for improving the electromigration reliability of lead-free interconnect solder joints based on ultrafast laser processing. The surface area of ​​the connection surface is increased by ultrafast laser processing of a special hexagonal array-shaped multi-scale micro-nano surface structure, which is beneficial to the uniform distribution of a series of solders and their mechanical bonding after solidification, so as to solve the problems of long processing time and poor reliability of existing lead-free interconnect solder joints.

[0004] In order to achieve the above object, the present invention provides a copper surface with a special hexagonal array microstructure, which is prepared by ultrafast laser processing technology. The preparation method is as follows:

[0005] A method for improving the electromigration reliability of lead-free interconnect solder joints based on ultrafast laser processing of hexagons, characterized in that an ultrafast laser processing process is used to prepare a hexagonal array groove microstructure on the end face of a to-be-interconnected solder body, the hexagonal array groove microstructure is composed of a plurality of independent hexagonal linear groove units, the hexagonal linear groove unit refers to a linear groove corresponding to the six sides of the hexagon, each side of each hexagonal linear groove unit is correspondingly provided with another hexagonal linear groove unit on the outside, the sides of two adjacent hexagonal linear groove units do not share a common side and there is a gap between them; micro-nano particles are densely distributed in and around the groove; the groove width is 30-50um, the depth is about 10-50um, the covered micro-nano particles form an overall structural feature of high porosity, the side length of each hexagon is 0.01mm-1mm, and then lead-free interconnect welding is used to improve the electromigration reliability.

[0006] Furthermore, the interconnected welding body is a copper rod, and a layer of grid-like groove multi-scale micro-nano structure is obtained on the end face of the copper rod through ultrafast laser processing technology. The SAC305 lead-free solder paste is filled between the two copper rods and then sintered at high temperature to form an interconnected structure.

[0007] Optionally, the selected copper rod is made of regular quadrangular prism-shaped polycrystalline copper with a cross-sectional side length of 0.6 mm and a length of 1 cm; the surface of the selected copper rod is polished to be smooth and flat, and then pickled with acetone solution and hydrochloric acid alcohol solution to remove organic matter and oxides attached to the surface of the copper rod to be welded.

[0008] Set the ultrafast laser processing parameters: scan times 5-20 times, laser power 10-50w, laser frequency 400kHz, and process hexagonal array structures;

[0009] Place the two treated copper rods on the PCB board, ensure that the welding plane is perpendicular to the PCB board, align the two welding planes and place them in parallel, keep the distance between the two welding planes at a preset distance, and use high-temperature silicone to fix the two treated copper rods. Then wait for the silicone to solidify, fill the solidified treated copper rods with solder balls, and then use a hot air gun to solder the copper rods to obtain the required linear solder joints;

[0010] Optionally, the solder uses SAC305 lead-free solder paste.

[0011] The prepared linear solder joints were subjected to electromigration tests, and samples were taken out at specific times to observe the microstructure of the samples. During the electromigration process, under the continuous action of a large number of electrons, the microscopic atoms in the solder joints undergo macroscopic migration. When the current density passing through the solder joint reaches the threshold value for electromigration (10 4 A / cm 2 ), the solder joint forms a cavity at the cathode, and then the cavity gathers and initiates microcracks, and finally the microcracks expand and cause the solder joint to crack, and the device fails to open the circuit. Therefore, the sudden increase of solder joint resistance is used as the failure criterion, and the failure time is recorded.

[0012] The advantage of the present invention is that a special surface structure can be obtained through ultrafast laser processing. The multi-scale hexagonal array micro-nano structure effectively increases the surface area of ​​the connection surface, which is beneficial to the uniform distribution of a series of solders and their mechanical bonding after solidification, so as to solve the problem of poor electromigration failure performance of existing linear solder joints. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following is a brief introduction to the drawings required for use in the embodiments. Obviously, the drawings described below are only some embodiments of this patent. For ordinary technicians in this field, other drawings can be obtained based on the following drawings without creative work.

[0014] Figure 1 This is a schematic diagram of the laser processing path;

[0015] Figure 2 Microstructure diagram of the copper rod after ultrafast laser processing; (a) top view (b) cross-sectional view.

[0016] Figure 3 Cross-sectional microstructure diagram of an ordinary linear weld and a linear weld processed by laser on the end face; (a) Cross-sectional view of a linear weld without laser processing (b) Cross-sectional view of a linear weld after laser processing.

[0017] Figure 4 This is a schematic diagram of the complete processing flow. DETAILED DESCRIPTION

[0018] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other. The described embodiments are only some embodiments of the present invention, not all embodiments. All other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. The present invention will be described in detail below with reference to the drawings and in combination with the embodiments.

[0019] The present invention will be further described below in conjunction with examples, but the present invention is not limited to the following examples.

[0020] Example 1: The following specifically describes the implementation method of the patent

[0021] 1. Preparation of copper rod: Use wire cutting to make a regular quadrangular prism-shaped polycrystalline copper rod with a size of 10 mm × 0.6 mm × 0.6 mm;

[0022] 2. Soak the copper rod in the prepared acetone solution and hydrochloric acid alcohol solution for a few minutes to remove organic matter and oxides on the surface of the copper substrate. After cleaning, use sandpaper to polish to ensure that the oxide layer is completely removed and the connection surface is flat. Polish after grinding and dry for later use;

[0023] 3. Fix the pre-treated copper rod with a fixture, and then place it horizontally on the processing platform with the end face facing upward. Adjust the platform height so that the end face is in the focal plane of the laser. Adjust the parameters of the ultrafast laser processing equipment so that the number of scans is 10 times, the laser power is 25w, and the laser frequency is 400kHz. Figure 1The graphics shown are processed;

[0024] 4. Next, place the two copper rods treated as above on the PCB board, with the welding plane perpendicular to the PCB board, using the laser processed surface as the welding plane, aligning the two welding planes and placing them in parallel, with the distance between the two welding planes maintained at 30um, and using high-temperature silicone to fix the two copper rods treated as above;

[0025] 5. Fill the soldering plane with SAC305 lead-free solder paste, place the device under a preheated hot air gun and heat it at 150°C and then 400°C for 60s respectively for soldering;

[0026] 6. Place the soldered structure in the electromigration tester and connect the circuit to 1.0×10 4 The electromigration failure performance test was carried out at a current density of A / cm2, and the failure criterion was that the solder joint resistance increased by 15% of the original value, and the failure time was recorded. The results are shown in Table 1 and Figure 3 .

[0027] Comparative Example 1: The following specifically describes the implementation method of the patent

[0028] The process is basically the same as that of Example 1 except that the ultrafast laser processing is not performed and the solder is directly filled between the pretreated copper rods.

[0029] The electromigration failure performance test of the connection structure is carried out, and the results are shown in Table 1.

[0030] Comparative Example 2: The following specifically describes the implementation method of the patent

[0031] Except for the ultrafast laser processing parameters in step 3, the rest is basically the same as in Example 1.

[0032] The parameters of the ultrafast laser processing equipment in this comparative example are: the side length of the scanning hexagon is 100um, the number of scans is 10 times, the laser power is 25w, and the laser frequency is 400kHz;

[0033] The electromigration failure performance test of the connection structure is carried out, and the results are shown in Table 1.

[0034] Comparative Example 3: The following specifically describes the implementation method of the patent

[0035] Except for the ultrafast laser processing parameters in step 3, the rest is basically the same as in Example 1.

[0036] The parameters of the ultrafast laser processing equipment in this comparative example are: the side length of the scanning hexagon is 60um, the number of scans is 20 times, the laser power is 25w, and the laser frequency is 400kHz;

[0037] The electromigration failure performance test was carried out on the connection structure. Table 1 records the total time from the start of power-on to the fracture failure of the linear solder joint.

[0038] Table 1 Electromigration performance test results of various connection structures

[0039] Connection structure Failure time / hour Example 1 217.4 Comparative Example 1 165.1 Comparative Example 2 198 Comparative Example 3 211.5

[0040] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for improving the electromigration reliability of lead-free interconnect solder joints based on ultrafast laser processing of hexagons, characterized in that: An ultrafast laser processing process is used to prepare a hexagonal array groove microstructure on the end face of the interconnected welding body. The hexagonal array groove microstructure is composed of multiple independent hexagonal linear groove units. The hexagonal linear groove unit refers to the six sides of the hexagon corresponding to the linear groove. Each side of each hexagonal linear groove unit is correspondingly provided with another hexagonal linear groove unit. The sides of two adjacent hexagonal linear groove units do not share the same side and there is a gap between them. Then lead-free interconnection welding is used to improve the electromigration reliability.

2. A method for improving the electromigration reliability of lead-free interconnect solder joints based on ultrafast laser processing of hexagons according to claim 1, characterized in that: The grooves and the surrounding areas are densely covered with micro-nano particles; the groove width is 30-50um, the depth is about 10-50um, and the side length of each hexagon is 0.01mm-1mm.

3. A method for improving the electromigration reliability of lead-free interconnect solder joints based on ultrafast laser processing of hexagons according to claim 1, characterized in that: The interconnect welding body is a copper rod. A layer of hexagonal array groove multi-scale micro-nano structure is obtained on the end face of the copper rod through ultrafast laser processing technology. The interconnect structure is formed by filling SAC305 lead-free solder paste between the two copper rods and sintering at high temperature.

4. A method for improving the electromigration reliability of lead-free interconnect solder joints based on ultrafast laser processing of hexagons according to claim 3, characterized in that: The selected copper rod is made of regular quadrangular prism-shaped polycrystalline copper, with a cross-sectional side length of 0.6 mm and a length of 1 cm. The surface of the selected copper rod is polished to be smooth and flat, and then pickled with acetone solution and hydrochloric acid alcohol solution to remove organic matter and oxides attached to the surface of the copper rod to be welded.

5. A method for improving electromigration reliability of lead-free interconnect solder joints based on ultrafast laser processing of hexagons according to claim 1, characterized in that: The ultrafast laser processing parameters were set to process a grid-like structure, and then the surface structure was observed through an optical microscope to confirm that it had a hexagonal array groove microstructure.

6. A method for improving electromigration reliability of lead-free interconnect solder joints based on ultrafast laser processing of hexagons according to claim 1, characterized in that: The two processed copper rods are fixed with thermally conductive silicone so that their processed end faces face each other and maintain a certain distance, and then they are waited for solidification, and solder is filled into the solidified processed copper rods, and then the copper rods are welded to obtain linear solder joints.

7. A method for improving electromigration reliability of lead-free interconnect solder joints based on ultrafast laser processing of hexagons according to claim 1, characterized in that: According to the preset spatial position, the method for fixing the two processed copper rods includes: placing the two processed copper rods on the PCB board, the welding plane is perpendicular to the PCB board, the two welding planes are aligned and placed in parallel, the distance between the two welding planes is maintained at a preset distance, and high-temperature silicone is used to fix the two processed copper rods.

8. A method for improving electromigration reliability of lead-free interconnect solder joints based on ultrafast laser processing of hexagons according to claim 1, characterized in that: The solder adopts SAC305 lead-free solder paste.

Citation Information

Patent Citations

  • Large-scale integrated interconnection electromigration failure test method

    CN102830338A

  • Copper interconnection functional microstructure and preparation method thereof

    CN109473418A

  • Method capable of controlling size of one-dimensional linear butt welding spot

    CN114012538A

  • Bionic honeycomb substrate for power device packaging and preparation method and application thereof

    CN118380392A

  • High-heat-conductivity diamond / metal joint and brazing method thereof

    CN119260095A